The Addition of Felsic Sediments to the Lower Continental Crust During the Variscan Orogeny - M. F. Ringwood; S. E. Ortner; R. L. Rudnick (Geochemistry, Geophysics, Geosystems)
Abstract Lower crustal metasedimentary xenoliths (garnet‐sillimanite granulites) from the Bournac breccia pipe in the Massif Central, France, provide a robust example of sediments transported to depth and incorporated into stable lower continental crust during a collisional orogeny. Dates for detrital igneous zircon range from the Archean (up to 3,300 Ma) to the Devonian and record sedimentation prior to the onset of the collisional phase of the Variscan orogeny. Metamorphic zircon and monazite document the presence of the metasediments in the lower crust by ca. 330 Ma during the later phase of Variscan collision. Zircon and monazite crystallization continued within the lower crust until ca. 265 Ma, corresponding to a period of slow cooling following an episode of ultra‐high temperature (UHT) metamorphism that peaked at 313 Ma. Zr‐in‐rutile thermometry and GASP barometry applied to these samples record conditions of 0.63–0.77 GPa and 830–910°C, which correspond to Ti‐in‐zircon temperatures from the latter part of the Variscan orogeny and geotherms in excess of typical continent‐continent collisions. Rutile in these samples remained open to Pb loss until their eruption at ca. 11.6 Ma, providing an indirect date of the Bournac eruption. These rocks record the incorporation of felsic sedimentary material into the stable deep continental crust during a collisional orogen and their residence there for over 300 Ma. More broadly, the addition of sediments to stable lower crust contributes to changes in crustal composition and has significant implications for the heterogeneity of the deep continental crust, as well as overall crustal heat production and mantle heat flow.